DYNAMIC EFFECTS IN A COMPOSITE TWO-COMPONENT RODS WHICH APPEAR WHEN LOCAL FRACTURE OF THE MATRIX IS OCCURRED - Kolchunov, Vitaly Ivanovich; Savin, Sergey Yurievich (Journal of Applied Engineering Science, 2017)
The article deals with the estimation of the dynamic increase of stresses in the element made of the composite two-component  material such as reinforced concrete, that appears when local destruction of the concrete matrix (crack formation) occurs. When the brittle fracture of the concrete occurs the stresses acting in the stretched concrete are transmitted to the reinforcing bars instantaneously that leads to longitudinal oscillations. In this moment stresses acting in the reinforcing bars can be higher than ultimate stresses. Hence progressive collapse of a structure is possible. It is presented general solution of the forced longitudinal oscillations problem. Displacement and stress increment equations are given. General solution is illustrated by analysis of a progressive collapse of a large-panel folded shell when local destruction of concrete matrix in the tightening element occurs.
Keywords: Longitudinal oscillations; Progressive collapse; Stresses; Matrix; Dynamics; Dynamic Effects; Concrete; Composition